1990
DOI: 10.1063/1.346863
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation of reactively sputtered amorphous W80N20 films

Abstract: The oxidation behavior of reactively sputtered amorphous tungsten nitride of composition W 80 N 20 was investigated in dry and wet oxidizing ambient in the temperature range of 450 ·c-575 ·c. A single W0 3 oxide phase is observed. The growth of the oxide follows a parabolic time dependence which is attributed to a process controlled by the diffusivity of the oxidant in the oxide. The oxidation process is thermally activated with an activation energy of 2.5 ±0.05 eV for dry ambient and 2.35 ±0.05 eV for wet amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The oxidation of W is thermodynamically favored and the formation of WO 3 is more favored than the formation of WO 2 . 27,59 The evaporation of WO 3 has been observed even at a low temperature of 550°C. 60 Thus in our growth temperature, WO 3 vapors readily evaporate into the gas phase.…”
Section: Resultsmentioning
confidence: 96%
“…The oxidation of W is thermodynamically favored and the formation of WO 3 is more favored than the formation of WO 2 . 27,59 The evaporation of WO 3 has been observed even at a low temperature of 550°C. 60 Thus in our growth temperature, WO 3 vapors readily evaporate into the gas phase.…”
Section: Resultsmentioning
confidence: 96%
“…The focus of the present work is the synthesis and physical characterization of tungsten oxynitride films. Tungsten nitrides have been widely studied for their use as diffusion barriers in microelectronics [18][19][20], gate electrodes in semiconductor devices [21,22], hard coatings to protect from mechanical wear [23][24][25], or as Schottky contacts [27]. Several of the early studies have contributed extensively towards the understanding of W-N system, especially the knowledge of fundamental relationship between different parameters, such as deposition conditions and their effect on the internal stress, microstructure, and elemental concentration [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tungsten nitrides have been widely studied for their use as diffusion barriers in microelectronics [18][19][20], gate electrodes in semiconductor devices [21,22], hard coatings to protect from mechanical wear [23][24][25], or as Schottky contacts [27]. Several of the early studies have contributed extensively towards the understanding of W-N system, especially the knowledge of fundamental relationship between different parameters, such as deposition conditions and their effect on the internal stress, microstructure, and elemental concentration [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Similarly, tungsten oxides have been studied for a wide variety of electrical, optical, and energy related applications [1][2][3][4][5][6][7][8][9][10][11][12] to longer wavelengths, and concluded that the conductivity of said films is lowered with increased nitrogen content [33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the case of amorphous barriers, the fast diffusion of oxygen through the barrier layer can be retarded at high temperatures due to its lack of grain boundaries. 36 It has been reported that the surface of the Ta-Si-N, amorphous ternary compound barrier is oxidized. The polycrystalline barriers possess the grain boundaries, which can act as fast diffusion paths as well as nucleation sites in forming various oxides.…”
Section: Resultsmentioning
confidence: 99%